2012
DOI: 10.1109/tgrs.2012.2194153
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Scattering Mechanism of Polarimetric SAR Signal From Mountainous Forest Areas

Abstract: International audienceThis study aims to understand the effects of the topographic slope variation on the vegetation backscattering characteristics of polarimetric imaging radar. Most of the previous studies in modeling microwave backscattering signatures of vegetated area have been carried out over relatively flat areas. In order to model vegetation scattering mechanisms of mountainous forests, this paper presents an improvement of the radiative transfer model that accounts for the tilted scattering surface b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…In mountainous forests, local topographic variations can lead to changes in the microwave scattering mechanisms [11][12][13]. Particularly, it has been reported that, among the radar backscattered signals, direct ground and vegetation-ground interactions can be significantly affected by the presence of topography [13].…”
Section: Open Accessmentioning
confidence: 99%
See 4 more Smart Citations
“…In mountainous forests, local topographic variations can lead to changes in the microwave scattering mechanisms [11][12][13]. Particularly, it has been reported that, among the radar backscattered signals, direct ground and vegetation-ground interactions can be significantly affected by the presence of topography [13].…”
Section: Open Accessmentioning
confidence: 99%
“…Particularly, it has been reported that, among the radar backscattered signals, direct ground and vegetation-ground interactions can be significantly affected by the presence of topography [13]. Consequently, the validity of the scattering models used in the target decomposition and relating slope-induced errors in the output of target decomposition techniques should be carefully evaluated in sloping forest areas.…”
Section: Open Accessmentioning
confidence: 99%
See 3 more Smart Citations